Case Report: The value of contrast-enhanced ultrasound and contrast-enhanced computed tomography in the diagnosis of hepatic angiosarcoma - Wang, Feiqian; Numata, Kazushi; Liang, Hua; Tsuchiya, Hiromi; Ruan, Litao; Tanabe, Mikiko; Bai, Xiaofang (Frontiers in Oncology, 2023)
Background: Enhanced imaging techniques have the overwhelming advantages of being noninvasive and sensitive enough to evaluate the microcirculation of lesions, thus making them accurate in the diagnosis of hepatic lesions. Unfortunately, there is very little research and knowledge about the imaging features of a rare cancerous condition: hepatic angiosarcoma (HA). Case summary: In this study, we retrospectively collected the data of six patients who underwent both contrast-enhanced ultrasound (CEUS) and contrast-enhanced computed tomography (CECT), and subsequently obtained a definitive histopathologic diagnosis of HA. We described the imaging appearances of HA by comparing CEUS and CECT images. Furthermore, we analyzed these imaging characteristics from the perspective of histopathology and tumorigenesis. The study included the largest number (six) of histopathologically confirmed HA patients who had received CEUS examinations to date. Conclusion: By offering readers comprehensive knowledge of contrast imaging, especially CEUS, in the diagnosis of HA, our study may reduce misdiagnosis and further improve treatment options.